In their voices : black Americans on transracial adoption - Roorda, Rhonda M., 1969- (Columbia University Press, 2015)
While many proponents of transracial adoption claim that American society is increasingly becoming colour-blind, a growing body of research reveals that for transracial adoptees of all backgrounds, racial identity does matter. Rhonda M. Roorda elaborates significantly on that finding, specifically studying the effects of the adoption of black and biracial children by white parents. She incorporates diverse perspectives on transracial adoption by concerned black Americans of various ages, including those who lived through Jim Crow and the Civil Rights era. All her interviewees have been involved either personally or professionally in the lives of transracial adoptees, and they offer strategies for navigating systemic racial inequalities while affirming the importance of black communities in the lives of transracial adoptive families.